Hemifacial microsomia: A case report - Kapur R; Kapur R; Sheikh S; Jindal S; Kulkarni S (Wolters Kluwer Medknow Publications, 2008)
Hemifacial microsomia is a congenital malformation in which there is a deficiency in the amount of hard and soft tissue on one side of the face. It is primarily a syndrome of the first branchial arch, involving underdevelopment of the temporomandibular joint, mandibular ramus, masticatory muscles and the ear. The affected ear may have an external soft-tissue malformation in addition to being lower set than on the contra lateral side. Hearing loss may result from underdevelopment of the osseous components of the auditory system and a diminished or absent external auditory meatus. Occasionally, second branchial arch defects involving the facial nerve and facial muscles coexist with Hemifacial microsomia. Radiographic examination in case of Hemifacial microsomia is of limited value because of superimposition of normal and abnormal bony structures. The skeletal and soft-tissue findings of a patient with Hemifacial microsomia who underwent three-dimensional computerized tomography is presented here to improve our knowledge and diagnostic skill of this uncommon entity.